Barre, Massachusetts. - O.H. Bailey & Co. (1891)
"O.H. Bailey & Co., lith. & pub., Boston."; Bird's-eye-view.; Includes views of Barre Plains, Crossleys, and Smithville, index to points of interest, and col.; Available also through the Library of Congress Web site as a raster image.; LC Panoramic maps (2nd ed.), 271.3